Expression and characterization of a cold-adapted lipase from an antarctic Pseudomonas sp. - Ganasen, Menega (2014)
Eleven strains of unknown microbial isolates obtained from Antarctica were screened for extracellular lipolytic activity. Eight isolates showed positive results on Tributyrin, Rhodamine B and Triolein agar plates. A single isolate (designated as strain AMS8) that demonstrated the highest lipase activity (0.056 U/mL) was finally used in the current research. It was identified as Pseudomonas sp. based on its morphological study and 16S rDNA analysis. A lipase gene (lipAMS8) was amplified from strain AMS8 via polymerase chain reaction (PCR) amplification. The open reading frame (ORF) of LipAMS8 is 1431 bp in length coding for 476 amino acids. LipAMS8 lacks an N-terminal signal peptide and contains a glycine- and aspartate-rich nanopeptide sequence at the C-terminus. The catalytic triad of LipAMS8 was predicted as Ser-207, Asp-255 and His-313, based on multiple sequence alignment. Both soluble and insoluble protein of LipAMS8 was expressed in Escherichia coli. The ORF of LipAMS8 was expressed using pTrcHis TOPO TA, pET-32b(+) and pGEX- 4T1, which are under the control of trc, T7lac and tac promoters, respectively. An optimum expression level for pTrcHis/lipAMS8, pET32b/lipAMS8 and pGEX/lipAMS8 under constant expression conditions was 0.346 U/mL, 6.066 U/mL and 1.533 U/mL, respectively. An improved lipase expression (9.493 U/mL) was attained using pET- 32b(+) vector in E. coli BL21(DE3) expressed at 15°C for 8 hours, induced with 0.05 mM isopropyl β-D thiogalactoside (IPTG) at E. coli growth optimal density of 0.5. Only a small amount of lipAMS8 was expressed in soluble form. A huge amount of expressed proteins were in the form of inclusion bodies or insoluble proteins. The inclusion bodies were solubilized by means of urea, a strong denaturating agent and are then refolded via single step dilution. The level of expression obtained from insoluble protein (41.84 U/mL) was almost four times higher compared to the soluble protein (9.493 U/mL). Crude enzyme obtained from intracellular inclusion bodies expression was then purified. The His-tagged recombinant LipAMS8 was purified with 23.0% total recovery and an average purification factor of 9.7. The purified LipAMS8 migrated as a single band with a molecular weight approximately 65 kDa during sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). LipAMS8 was highly active at 30°C and pH 10. It retained almost 19 and 68% of its relative activity at 0 and 10°C, respectively. The half-life of LipAMS8 was 4 and 2 hours at 30 and 40°C, respectively. The lipase was stable over a broad range of pH (pH 6 to 12). LipAMS8 showed enhancement effect in its relative activity under the presence of Li+, Na+, K+, Rb+ and Cs+ after 30 minutes treatment. Nonetheless, the enhancement effect decreases as the metallic character increases from Li+ to Cs+. As for divalent metals, a lower concentration (1 mM) of Mg2+ and Ca2+ gave an enhancement effect to the LipAMS8 activity after 30 minutes treatment. Heavy metal ions such as Cu2+, Fe3+ and Zn2+ inhibited LipAMS8 activity. As for the organic solvent, methanol, ethanol and xylene had almost no effect on lipase activity, whereas β-mercaptoethanol, pyridine, 1-butanol, iso-amylalcohol, propylacetate and 1-propanol exhibited an inhibitory effect. The LipAMS8 demonstrated high stability in the presence of dimethylsulfoxide, isooctane, octane, n-decane, n-tridecane, n-tetradecane and n-hexadecane. In conclusion, a new cold-adapted lipase was successfully isolated and its nucleotide sequence was deposited at gene bank under the accession number HQ162821. It exhibited stability and activity at broad range of pH, elevated temperatures and also in the presence of certain metal ions and organic solvents. These unique properties of LipAMS8 will provide considerable potential for many biotechnological and industrial applications.